The Relationship Between Adversity Quotient and Anxiety in Facing the World of Work in Class XII Students at Semen Padang Vocational School - Aulia, Valerina Sindy; Free Dirga Dwatra (Causalita, 2025)
This research aims to determine the relationship between adversity quotient and anxiety in facing the world of work, as well as how the dimensions of the adversity quotient are related to anxiety in facing the world of work. The high rate of open unemployment among vocational school graduates causes anxiety in the transition to the world of work. Adversity quotient, as an individual's ability to face challenges, is thought to have a role in managing anxiety. The analytical method used in this research is a quantitative method with a correlational design. The research subjects were 62 class XII students at Semen Padang Vocational School who were selected using a total sampling technique. The instruments used are an adversity quotient scale and an anxiety scale with a Likert model. The analysis used is multiple linear regression analysis with SPSS 25. The results show that the adversity quotient of control has a significant positive relationship with a value of p= 0.014, the origin & ownership dimension and the reach dimension have a significant negative relationship with anxiety in facing the world of work with a value of p= 0.022 and p= 0.018, while the endurance dimension has no relationship with anxiety in facing the world of work with a value of p= 0.113. Therefore, it is hoped that this research can make a contribution to the field of educational psychology, especially in designing programs that can increase students' adversity quotient to help them face the world of work with more confidence.